2018
DOI: 10.1098/rsfs.2018.0009
|View full text |Cite
|
Sign up to set email alerts
|

Control of gaze in natural environments: effects of rewards and costs, uncertainty and memory in target selection

Abstract: The development of better eye and body tracking systems, and more flexible virtual environments have allowed more systematic exploration of natural vision and contributed a number of insights. In natural visually guided behaviour, humans make continuous sequences of sensory-motor decisions to satisfy current goals, and the role of vision is to provide the relevant information in order to achieve those goals. This paper reviews the factors that control gaze in natural visually guided actions such as locomotion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Second, a number of studies have highlighted that spatial positioning plays a strong role in guiding search towards objects when finding objects in both 2D scene images (Castelhano & Heaven, 2011;Malcolm & Henderson, 2010;Pereira & Castelhano, 2019;Võ & Henderson, 2009;Williams & Castelhano, 2019) and virtual 3D environments (Hayhoe & Matthis, 2018;Kit et al, 2014;Li, Aivar, Kit, Tong, & Hayhoe, 2016;Li, Aivar, Tong, & Hayhoe, 2018). Thus, it seems reasonable that the depth at which the information occurs would also play a role when searching in a real environment.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a number of studies have highlighted that spatial positioning plays a strong role in guiding search towards objects when finding objects in both 2D scene images (Castelhano & Heaven, 2011;Malcolm & Henderson, 2010;Pereira & Castelhano, 2019;Võ & Henderson, 2009;Williams & Castelhano, 2019) and virtual 3D environments (Hayhoe & Matthis, 2018;Kit et al, 2014;Li, Aivar, Kit, Tong, & Hayhoe, 2016;Li, Aivar, Tong, & Hayhoe, 2018). Thus, it seems reasonable that the depth at which the information occurs would also play a role when searching in a real environment.…”
Section: Discussionmentioning
confidence: 99%
“…1). Participants were recruited based on (1) having normal or contact-corrected vision and no colorblindness, (2) having no neurological or psychiatric conditions, and 3 Eye-tracker specifications and accuracy. A monocular, in-headset eye-tracker (Pupil Labs: 120 Hz sampling frequency, 5.7 ms camera latency, 3.0 ms processing latency; 0.6 visual degrees accuracy, 0.08 visual degrees precision) continuously monitored the position of participants' right eye during scene viewing.…”
Section: Participantsmentioning
confidence: 99%
“…Constructing a sense of place in a complex, dynamic environment is an active process. Humans actively sample their sensory environment to build an understanding of their surroundings and gain information relevant to their behavioral goals 1,2 . Yet, much of what we know about how people encode real-world environments comes from paradigms that severely limit participants' active affordances: paradigms in which head-restricted participants view images that are passively displayed on a computer screen.…”
mentioning
confidence: 99%
“…During novel tool use [34,20] found that in actors and observers, respectively, prior knowledge and uncertainty alter problem solving. Uncertainty in eye movements has been examined both during cognitive decisions [15], problem solving while copying a model [3], outdoor navigation [17] and driving [46]. However, to our knowledge there have been no prior attempts to combine egocentric video, eye movement data, and frame-by-frame uncertainty ratings for a complex extended task like ours.…”
Section: Related Workmentioning
confidence: 99%